2009
DOI: 10.1002/hon.903
|View full text |Cite
|
Sign up to set email alerts
|

Continuous infusion idarubicin and intravenous busulphan as conditioning regimen to autologous stem cell transplantation for patients with acute myeloid leukaemia

Abstract: The current study aimed to evaluate the efficacy and toxicity of a combination of intravenous (iv) busulfan (Bu) and continuous infusion Idarubicin (IDA) as a conditioning regimen to autologous haematopoietic stem cell transplantation (ASCT) in patients with acute myeloid leukaemia (AML). The protocol included IDA at 20 mg/sqm daily as 3 days continuous infusion (from day -13 to -11) and intravenous BU at 3.2 mg/kg daily from day -5 to -2. Patients aged over 60 years received a reduced schedule (2 days IDA and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…35,36 Using the same regimen, researchers in Nanjing Relevant to this study, an EBMT retrospective analysis showed that the use of G-CSF after ASCT is not associated with an increased risk of relapse. 39 The BEAM regimen has been recently advocated for T-cell ALL by the Russian ALL study group, 40 and treatment with TKI for Ph In vivo purging, MRD quantification and graft quality In the past decade numerous studies on adults and children with AML or ALL have reported that patients who achieve CR1, with no detectable MRD 41 evaluated after induction or conventional consolidation, have a significantly better outcome compared with MRD-positive patients.…”
mentioning
confidence: 77%
“…35,36 Using the same regimen, researchers in Nanjing Relevant to this study, an EBMT retrospective analysis showed that the use of G-CSF after ASCT is not associated with an increased risk of relapse. 39 The BEAM regimen has been recently advocated for T-cell ALL by the Russian ALL study group, 40 and treatment with TKI for Ph In vivo purging, MRD quantification and graft quality In the past decade numerous studies on adults and children with AML or ALL have reported that patients who achieve CR1, with no detectable MRD 41 evaluated after induction or conventional consolidation, have a significantly better outcome compared with MRD-positive patients.…”
mentioning
confidence: 77%
“…Following consolidation, G-CSF at 10 mg/kg was given from day 15 with the aim of shortening neutropenia and mobilizing CD34þ cells. In all patients with successful collection of CD34þ cells (!2 Â 10 6 /kg) ASCT was programmed with conditioning regimen consisting of high dose CI idarubicin plus busulphan, as previously described [20,21]. A PS < 3, absence of active infection and/or severe organ damage were required to be considered for ASCT.…”
Section: Treatment Designmentioning
confidence: 99%
“…BU and continuous infusion IDA as a conditioning regimen for auto-SCT in patients with AML and a better outcome was found. [16][17][18][19] Therefore, we investigated combinations of BU with IDA instead of BUCY2 as a myeloablative conditioning regimen that may result in effective and well-tolerated myeloablative conditioning regimens. Here, we report the results obtained in our institute retrospectively by comparing standard vs IDA-intensified BUCY2 (IDA-BUCY2) myeloablative conditioning regimens in allo-PBSCT for high-risk hematological malignancies over a period of several years.…”
Section: Introductionmentioning
confidence: 99%